Deamination of N→Sn‐Coordinated Organotin(II) Hydroxide: Formation of a New C–O Covalent Bond. Issue 31 (2nd October 2014) - Dostál, Libor; Růžička, Aleš; Jambor, Roman
Abstract: The synthesis of the pentacarbonylchromium complex [{2, 6‐(Me2 NCH2 )2 C6 H3 }(Cl)SnCr(CO)5 ] is reported. Starting with this compound, organotin(II)pentacarbonylchromium methoxide [{2, 6‐(Me2 NCH2 )2 C6 H3 }(OMe)SnCr(CO)5 ] was prepared and used for the synthesis of dimeric N→Sn intramolecularly coordinated organotin(II)pentacarbonylchromium hydroxide [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(μ‐OH)Cr(CO)5 ]2 by easy hydrolytic protocol. In addition, acid–base‐type reaction of this latter compound with HOTf provided unprecedented cyclization product [6‐(Me2 NCH2 )‐2, 3‐(C6 H3 CH2 OSn)Cr(CO)5 ]2 . The cyclization process is accompanied by the formation of a new C–O covalent bond along with the elimination of Me2 NH. Abstract : An acid–base‐type reaction of N→Sn intramolecularly coordinated organotin(II)pentacarbonylchromium hydroxide [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(μ‐OH)Cr(CO)5 ]2 with trifluoromethanesulfonic acid (HOTf) provided unprecedented cyclization product [{6‐(Me2 NCH2 )‐2, 3‐(C6 H3 CH2 OSn)}Cr(CO)5 ]2 . The cyclization process is accompanied by the formation of a new C–O covalent bond along with the elimination of Me2 NH.